News records of ferns and lycophyte to the state of Paraiba, northeastern Brazil - Leandro Costa Silvestre; Juan Diego Silva Lourenço; Nathally Mola Pessoa Braga; Sergio Romero da Silva Xavier (Biotemas, 2013)
New records are presented of the occurrence of five ferns and a lycophyte for the state of Paraiba.